Stochastic Trends and Economic Fluctuations - King, Robert G.; Plosser, Charles I.; Stock, James H.; Watson, Mark W. (American Economic Review, 1991)
Are business cycles mainly the result of permanent shocks to productivity? This paper uses a long-run restriction implied by a large class of real-business-cycle models–identifying permanent productivity shocks as shocks to the common stochastic trend in output, consumption, and investment–to provide new evidence on this question. Econometric test indicate that this common-stochastic-trend / cointegration implication is consistent with postwar U.S. data. However, in systems with nominal variables, the estimates of this common stochastic trend indicate that permanent productivity shocks typically explain less than half of the business-cycle variability in output, consumption, and investment.